Exploring Future Research in Physical Education: Espousing a Social Justice Perspective. Issue 4 (2nd October 2019) - Walton-Fisette, Jennifer L.; Richards, K. Andrew R.; Centeio, Erin E.; Pennington, Todd R.; Hopper, Tim
ABSTRACT: Although there has been forward movement in identifying and addressing diverse learning needs, social justice education is not a significant part of the current standards for beginning teachers or K-12 students in the U.S. Throughout our standards-based history, social justice has been more of a hidden curriculum. To attain the 50 Million Strong by 2029 goal, it is vital to acknowledge that physical education is a social justice issue. Without consideration of the historical, political, and social contexts that permeate and frame physical education, along with the social identities and lived experiences of our future teachers and students, it is unlikely that this goal will be sustained. While concerns have been voiced relative to the standards-based teaching movement, in a country that espouses standards-based education, a first step in moving any educational reform forward is to formalize its inclusion in the national standards that serve to guide our discipline. A philosophical shift may be what is needed for change to occur regarding social justice education in an attempt to enhance the learning opportunities for all students. A forward step in creating this change is to address the research and pedagogical practices of our current physical education teacher education and K-12 programs, along with the physical education standards and policies at the national and state levels. We specifically articulate connections between social justice education and four key, interconnected research areas related to (a) occupational socialization, (b) curriculum, instruction, and assessment, (c) technology, and (d) professional development.